The IL-2-STAT5 pathway is blocked in chronic lymphocytic leukemia cells - Matveeva, A.; Kovalevska, L.; Polischuk, A.; Kashuba, E. (Онкологія, 2017)
Aim: to study the status of the interleukin-2 (IL-2) pathway in chronic lymphocytic leukemia (CLL) cells, to understand functional differences between CLL and
the normal mature B-cells. Objects and methods: samples of peripheral blood of
patients with CLL, RNA isolation, analysis of expression of transcription factors,
using RT2 profiler assay and quantitative polymerase chain reaction, bioinformatics analysis of publicly available data bases on expression. Results: we have found
that the JAK-STAT5 pathway is largely inactivated in CLL cells. Despite elevated expression of STAT2 and STAT5 genes at the mRNA level, STAT5-responsive
genes, such as BCL2L1 (BCL-XL), CCND2 (Cyclin D2), HIF1A, ID1, MCL1,
and MYC are down-regulated in CLL cells, compared to peripheral blood B-cells
of healthy individuals. Conclusions: the inactivation of the JAK-STAT5 pathway
could be explained by the high levels of soluble IL-2RA, as was reported earlier.
Another possibility could be inhibition of STAT5 phosphorylation, leading to inability to form the active transcriptionally protein heterodimers. The phosphorylation status of STAT proteins in CLL cells should be further illuminated. Мета: вивчити стан шляху інтерлейкіну-2 (IL-2) у клітинах хронічного лімфоцитарного лейкозу (ХЛЛ), щоб зрозуміти функціональні відмінності між ХЛЛ і зрілими B-клітинами. Об’єкти
і методи: зразки периферичної крові хворих наХЛЛ,
ізоляція РНК, аналіз експресії транскрипційних
факторів із використанням аналізу плати RT2
та кількісної полімеразної ланцюгової реакції, біоінформатичний аналіз загальнодоступних баз даних щодо експресії генів. Результати: виявлено,
що сигнальний шлях JAK-STAT5 переважно інактивований в клітинах ХЛЛ. Незважаючи на підвищену експресію генів STAT2 та STAT5 на рівні
мРНК у клітинах ХЛЛ експресія генів, які трансактивуються STAT5, таких як BCL2L1 (BCL-XL),
CCND2 (циклін D2), HIF1A, ID1, MCL1 та MYC,
знижена порівняно з цим показником у В-клітинах
периферичної крові здорових донорів. Висновки:
інактивація шляху JAK-STAT5 може бути пояснена високим рівнем розчинного IL-2RA, як було
показано раніше. Також є можливим інгібування фосфорилювання протеїну STAT5, що робить
неможливим утворення гетеродимерів білків, які
є транскрипційно активними. Стан фосфорилювання білків STAT у клітинах ХЛЛ потребує додаткового вивчення.